Public Procurement in Zambia: A Commentary on the Law and Practice - Mwamba, Gilbert K (IJRDO - Journal of Business Management, 2017)
Since the enactment of The Public Procurement Act No. 12 of 2008, scholarly analyses and evaluations of its contents, institutional mechanisms and underlying policy objectives are conspicuously absent. This seminal article on the subject seeks to outline and discuss the institutional and legal framework for the public procurement system and practice in Zambia. Thus, government agencies, procurement officers, anti-corruption institutions, policy-makers, scholars, students, judges and lawyers in Zambia will find this article most invaluable for practice.